Higher Leverage and Lower Profitability in Indonesian Food and Beverage Companies : Rasio Utang yang Lebih Tinggi dan Profitabilitas yang Lebih Rendah pada Perusahaan Makanan dan Minuman di Indonesia - Dita Charolina Evangelista Cahyani Arianto; Muhadjir Anwar (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Profitability is a central indicator of corporate financial performance, while liquidity, capital structure, and firm size represent key internal financial characteristics. Specific Background Indonesian Food and Beverage companies experienced a decline in average Return on Assets from 5.28% in 2022 to 2.39% in 2025, increasing the relevance of examining internal financial determinants. Knowledge Gap Prior studies report inconsistent findings regarding liquidity and capital structure, suggesting that contextual factors, including firm size, require further examination. Aims This study examines liquidity and capital structure in relation to profitability, with firm size as a moderating variable, among Food and Beverage companies listed on the Indonesia Stock Exchange during 2022–2025. Using secondary financial-statement data, 252 observations were initially selected through purposive sampling, with 223 retained after outlier elimination and analyzed using Moderated Regression Analysis. Results Liquidity was not significant (β = 1.631; p = 0.076), whereas capital structure showed a negative significant coefficient (β = −2.304; p = 0.001). Firm size weakened the liquidity–profitability relationship (β = −1.929; p = 0.004) but did not moderate the capital structure–profitability relationship (β = −0.775; p = 0.084). The model explained 26.7% of profitability variation. Novelty The study tests firm size as a contextual moderator of two financial determinants within the 2022–2025 Indonesian Food and Beverage subsector. Implications The findings support careful debt management and indicate that asset scale does not remove the profitability consequences associated with capital structure. Highlights: Current ratio was statistically nonsignificant at β = 1.631 and p = 0.076. Debt-to-equity ratio recorded a negative significant coefficient of −2.304 at p = 0.001. Firm size weakened the current-ratio–ROA linkage but did not moderate the debt-to-equity–ROA linkage. Keywords: Liquidity, Capital Structure, Firm Size, Profitability, Moderated Regression Analysis